Pengaruh Kepercayaan pada Komitmen Loyalitas Pelanggan - Lita, Ratni Prima (Jurnal Trikonomika, 2009)
The purposes of this study are to analyze; the influence of customer trust toward customer commitment; the influence of customer trust toward customer loyalty; and the influence of customer commitment toward customer loyalty. This study uses management science approach especially the service marketing and consumer behavior. The type of this research is descriptive and verificative, while the methods used both descriptive and explanatory survey. Investigation type is causality and time horizon is cross sectional, using convinience sampling technique. The sample size was 100 of hotel user at West Sumatera. The data analyzed by descriptive analytic and Structural Equation Model. The results of study show that customer trust have significant influence toward customer commitment; customer trust have not significant influence toward customer loyalty; and customer commitment have significant influence toward customer loyalty.